2021
DOI: 10.3390/en14030594
|View full text |Cite
|
Sign up to set email alerts
|

Energy Optimization of Electric Vehicles by Distributing Driving Power Considering System State Changes

Abstract: In a battery-electric vehicle, a representative electric vehicle, there is a growing demand for performance and one-charge mileage improvement. As an alternative to such improvements, the capacity of the battery has been increased; however, due to the corresponding increase in the weight of the battery and the limited space in the vehicle, increasing the capacity of the battery also has limitations. Therefore, researches are being actively conducted to improve system operation efficiency to overcome such limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…A battery for a longdistance vehicle needs to be considered that has more capacity and power, can travel extremely far, and can supply the final miles of the vehicle's driving range. The vehicle must be able to quickly locate the battery-charging station [61]. However, because using clean energy is less expensive than conventional energy in the beginning, operators will be able to minimize energy expenses by investing in cars that employ clean energy technology.…”
Section: Requirements Specification Of the Busmentioning
confidence: 99%
“…A battery for a longdistance vehicle needs to be considered that has more capacity and power, can travel extremely far, and can supply the final miles of the vehicle's driving range. The vehicle must be able to quickly locate the battery-charging station [61]. However, because using clean energy is less expensive than conventional energy in the beginning, operators will be able to minimize energy expenses by investing in cars that employ clean energy technology.…”
Section: Requirements Specification Of the Busmentioning
confidence: 99%
“…In order to propose an optimization algorithm for the driving patterns to achieve maximum efficiency energy, it is important to understand the traction management and the energy consumption flow, from the battery to the EV wheels. In addition, the power conditions and limitations of battery discharge EV during its operation were considered as studies showed in [43,44]. Figure 8 shows an overall diagram where each subsystem is interconnected.…”
Section: Energy Efficiency Optimizermentioning
confidence: 99%
“…Transportation via fuel cell electric vehicles (FCEVs), fuel cell hybrid electric vehicles (FCHEVs) and battery electric vehicles (BEVs) have gained popularity. However, BEVs that use the battery pack as the main power has some drawbacks such as the short driving range [2], the battery requires hours to fully charge [3] and high cost and weight of BEVs due to their large battery packs [4]. Meanwhile, FCEVs have also some disadvantages such as dynamic response is slow as well as a high hydrogen cost, and the inability to recharge by the principle of regenerative braking energy [5].…”
Section: Introductionmentioning
confidence: 99%